Students’ perception on the effectiveness of flex-it! in building confidence in communicating in English / Nur Aziela Aidit ... [et al.] - Aidit, Nur Aziela; Morni, Affidah; Nik Fauzi, Sheela Faizura; Muhammad Azmi, Safrina (2022)
Speaking is regarded as the most anxiety-inducing skill in language learning where most ESL learners tend to feel uncomfortable when speaking in the target language due to various reasons. This has led the students to develop low self-confidence when they are required to speak English. As a result, they have inadequate ability to communicate well in English which is believed to be one of the contributing factors to poor employability once they graduate from the tertiary institutions. Thus, Flex-It was designed to enhance the students’ speaking skills in English and build confidence in expressing their ideas in the target language. Flex-It is a fun and interactive card game designed to provide the opportunity for ESL learners to construct and express their ideas creatively in the target language. This card game focuses on the use of common language functions in different situational contexts that are usually applied in real-life situations, i.e., outside of the classroom context. There are three different sets of cards, namely, one set of language function cards, one set of chance cards, and one set of situation cards. To stimulate the players’ interest, the players were given two tokens for each correct expression used within one minute. The player who collects the most tokens and finishes their language function cards the fastest will be the winner. Through this game, it was discovered that the ESL learners were able to construct sentences based on the given situation by incorporating appropriate language functions. At the same time, they were also able to improve all the language skills needed and promote turn-taking skill among the players. To conclude, Flex-It is an interactive teaching tool which can be used to lower the learners’ anxiety level and enhance their speaking ability when communicating in English.